A comparative study of morbidity pattern among term and late preterm infants in a tertiary care hospital - Haridas, Kiran; Shinde, Rajendra; Nagar, Pritesh; Parakh, Hemant (International Journal of Contemporary Pediatrics, 2019)
Background: The incidence of preterm birth, defined as delivery before the end of the 37th week of pregnancy from the first day of the last menstrual period, is increasing. India accounts for the 40% of the global burden of low birth weight babies with 7.5million babies born with a birth weight of <2500g. The objective of the study is to compare the morbidity suffered by the late preterm infants with that of term infants. Methods: This was a retrospective study and the data for this study came from the medical records of maternal and neonatal case sheets and discharge summaries. The data was collected for the period between January 2014 and December 2014. All the late preterm infants born and admitted during early neonatal period were compared with term infants who were born and admitted during early neonatal period to the Aditya Hospital on the basis of maternal, infant and clinical characteristics. Results: A total 292 infants including LPTI and term infant records were obtained. LPTI group had significant problems compared to term infants. The predominant clinical problems at birth and during the early neonatal period are neonatal jaundice, transient tachypnea of newborn, feeding difficulty and probable sepsis. Conclusions: LPTI are at increased risk of morbidity compared to term infants and hence require special attention and care for possible complication during their early neonatal period.